Conservation Genetics of an Endangered Lady’s Slipper Orchid: Cypripedium japonicum in China - Qian, Xin (MDPI, 2014)
Knowledge about the population genetic variation of the endangered orchid, Cypripedium japonicum, is conducive to the development of conservation strategies. Here, we examined the levels and partitioning of inter-simple sequence repeat (ISSR) diversity (109 loci) in five populations of this orchid to gain insight into its genetic variation and population structure in Eastern and Central China. It harbored considerably lower levels of genetic diversity both at the population (percentage of polymorphic loci (PPL) = 11.19%, Nei’s gene diversity (H) = 0.0416 and Shannon’s information index (I) = 0.0613) and species level (PPL = 38.53%, H = 0.1273 and I = 0.1928) and a significantly higher degree of differentiation among populations (the proportion of the total variance among populations (Φ(pt)) = 0.698) than those typical of ISSR-based studies in other orchid species. Furthermore, the Nei’s genetic distances between populations were independent of the corresponding geographical distances. Two main clusters are shown in an arithmetic average (UPGMA) dendrogram, which is in agreement with the results of principal coordinate analysis (PCoA) analysis and the STRUCTURE program. In addition, individuals within a population were more similar to each other than to those in other populations. Based on the genetic data and our field survey, the development of conservation management for this threatened orchid should include habitat protection, artificial gene flow and ex situ measures.